Becoming a language teacher: Exploring the transformative potential of blogs. (October 2017) - Arshavskaya, Ekaterina
Abstract: Over the last two decades, Internet and advances in technology more generally have allowed to support and enhance teacher learning in both school and university contexts. Computers and other technological innovations have created more collaborative learning environments, expanded the contexts of teacher communication, and facilitated teacher engagement with digital literacy such as blogging. This paper presents case studies of two pre-service language teachers involving analysis of the teachers' blogs and interviews. Developmental trajectories of the participating pre-service teachers during one academic semester (15 weeks) are analyzed through the lens of transformative learning theory. The transformative learning theory allows to investigate the ways in which teachers change (or, transform) through the activity of writing. The analysis reveals that some pre-service teachers may not always react positively to the requirement to maintain a teacher blog and such lack of involvement prohibits teacher transformation. The study suggests that teacher educators provide more guidelines regarding blogging to more reluctant participants or even offer alternative arrangements such as, for example, face-to-face meetings. Lastly, the paper argues for greater consideration of adult learning and adult development theories as a basis for furthering our understanding of and fostering teacher learning. (193 words).